Resilience of Indian cattle in changing climate - Divya, Devara; Kumar, Sushil; Das, A. K.; Kumar, Ravinder (Indian Farming, 2024)
This article describes the present condition and prospects of India's indigenous cattle breeds within the framework of climate change. It highlights the dwindling numbers of indigenous breeds attributed to the widespread use of exotic semen and a preference for imported breeds, which has eroded the distinctive qualities of our diverse breeds across different agro-climatic regions needed to meet increasing productivity demands. Additionally, it outlines the impact, adaptation mechanisms, and strategic approaches concerning climate change, concluding that urgent measures such as effective breeding practices and conservation initiatives are imperative to safeguard India's unique cattle breeds and fortify their resilience.